Peci Oren, “Peer Coaching for Teen”: A Strategy to Reduce Gaming Disorder in Adolescents - Aura Aulia; Laela Khosiyah; Firos Javier Alzena; Candra Dewi Rahayu (Center for Intellectual Property and Technology Innovation, Universitas Sains Al-Qur'an, 2025)
Problem Statement The rapid development of information and communication technology has a significant impact on adolescent behavior, one of which is online game addiction. Online games, which have become one of the favorite entertainments for teenagers, have led to the emergence of the phenomenon known as gaming disorder, which is characterized by an uncontrollable pattern of gaming behavior. Objective This study aims to analyze the risk factors of gaming disorder in adolescents, as well as to explore its management efforts through the PECI OREN (Peer Coaching For Teens) method. Method The research was conducted using a descriptive-analytic design, involving 86 high school students at risk of experiencing gaming disorder. The instrument used to measure gaming disorder symptoms is the Internet Gaming Disorder Scale–Short-Form (IGDS9-SF). Finding The research results show that 11.6% of respondents are at risk of experiencing gaming disorder, with the highest score found in the symptom of